Wafer Nutrient with the Addition of Rubber Seed Flour (Hevea brasiliensis) and its Effect on Local Goat Performance - Triani Adelina; Anwar Efendi Harahap; Arsyadi Ali; Hidayati Hidayati; Dewi Ananda Mucra; Bayu Nuari Ramadhan; Nashihul Ulwan (Faculty of Animal Science, Universitas Gadjah Mada, 2021)
Local goats are one of the ruminants that have several advantages, including being expose to extreme temperatures such as in the tropics and can withstand to various types of diseases. Information regarding studies for wafer with the addition of rubber seed for goat is still limited. This study aims to determine the performance of local goats which is given wafer addition of rubber seed flour (RSF). The research parameters measured for wafer nutrient including dry matter, crude protein, crude fiber, ether extract and ash, while the performance of local goats wafers included feed intake, bodyweight gain, and feed efficiency. Twelve local goats were selected and they were assigned to 4 groups of treatments of three each in a randomized complete block design (RCBD). The 4 diets treatment were wafers added with rubber seeds flour of 0%, 7%, 14% and 21%. The results showed that the addition of rubber seed flour in wafer had effect (P<0.05) on the dry matter, crude protein, crude fiber, ether extract and ash but no significant effect (P>0.05) the feed intake, bodyweight gain, and feed efficiency. It can be conclude that the use of wafers until 21% rubber seed flour can improve the nutrient content of wafers but can not improve the production performance of local goats.